2022
DOI: 10.1097/prs.0000000000010120
|View full text |Cite
|
Sign up to set email alerts
|

“Gender and Ethnic Diversity in Plastic Surgery: Temporal Trends Among Speakers at National and Regional Plastic Surgery Conferences”

Abstract: Background: Scientific leadership among women and underrepresented minorities is lacking in plastic surgery. It is unknown whether the underrepresentation of women and ethnic minorities extends into academic conferences. The authors evaluated the temporal trends of female and ethnic minority representation at plastic surgery conferences in the United States. Methods: A retrospective analysis of all presentations from seven national and regional plastic surgery meetings between 2014 and 2018 was conducted. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Tolson et al 125 reported that Whites and Asians were overrepresented in plastic surgery societies and editorial boards. Landford et al 122 found that Asians were overrepresented as first authors (27% vs 12% in workforce).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tolson et al 125 reported that Whites and Asians were overrepresented in plastic surgery societies and editorial boards. Landford et al 122 found that Asians were overrepresented as first authors (27% vs 12% in workforce).…”
Section: Resultsmentioning
confidence: 99%
“…Landford et al 122 reported a greater representation by women as presenters at plastic surgery meetings (34%) than in the workforce (17%). Jacobson et al 123 reported that the proportion of female speakers at hand surgery meetings increased from 4% to 19% between 2010 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations